Critical thinking in teaching arabic as a foreign language; teacher’s competence - Mohamed Nor, Hanzalah (Human Resource Management Academic Research Society, 2022)
Critical thinking is acknowledged as one of the important skills that is essential in the 21st century education. Although critical thinking is not on the mandated list of educational goals in Arabic language teaching, it has been understood as the learning outcome of all lessons. Given the importance of critical thinking, it is crucial to have a thorough grasp of what it entails. The majority of critical thinking research looks at students' critical thinking ability using a quantitative instrument that operationalizes a certain conceptualization. However, there is still limited study on the strategies used by teachers in enhancing students’ critical thinking skills. The lack of such understanding makes it difficult to design effective teaching strategy and interventions. The purpose of this qualitative study is to explore the elements of personal competency that Arabic language teachers need to encourage critical thinking in the classroom. In this study, semi-structured interviews were conducted on six experts in the Arabic language education at secondary school and public university. Transcriptions of the data were analyzed to generate matrix tables and themes through NVivo version.12. The findings revealed four primary themes through thematic analysis of the interview transcripts represented by 15 subthemes in terms of teacher’s personal competences; (i) content mastery competence; (ii) pedagogical competence; (iii) communication competence, and (iv) organizational competence. However, the ways in which these themes appeared varied considerably among the experts. These results point to the variety of ways in which teachers can be expected to think critically. In respect to the findings of this study, some recommendations have been proposed for upcoming researches underpinning critical thinking competence as the main focus include the diversity of research type and data analysis techniques.